The removing of selected pharmaceuticals on WWTP in the Czech Republic - Wanner, F.; Vana, M.; Matousova, L.; Fuksa, J.K.; Pospichalova, D. (Химия и технология воды, 2016)
In this article, the results of three years monitoring of selected pharmaceuticals (diclofenac, ibuprofen, carbamazepine, salicylic acid, clofibric acid) in the wastewaters of the Czech Republic are presented. The monitoring was performed on selected Wastewater Treatment Plants (WWTP) with various treatment technology and designed capacity. The concentrations and treatment efficiency of these substances were observed in various profiles of each WWTP, including influent, mechanical pretreatment, biological treatment, effluent. The main processes of removing selected pharmaceuticals during wastewater treatment are discussed. These results are used for design wastewater treatment technology with improved treatment efficiency of these substances.